PENGARUH SUHU, LAMA PEMASAKAN, KONSENTRASI METANOL DAN SUHU PEMURNIAN TERHADAP BILANGAN IOD DAN BILANGAN ASAM SURFAKTAN DARI MINYAK INTI SAWIT - Hidayati, Sri (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2007)
Methyl Ester Sulfonates surfactant is produced from sulphonation process between methyl ester and sulphonating agent, such as NaHSO3. The purpose of these research were to obtain the optimum conditions (reaction temperature, sulphonation time, methanol concentration and purification temperature) of sulphonation process in producing MES from Palm Kernel Oil methyl ester and to investigate the characteristic of MES produced. Measurements conducted included iodine value and acid value. The experimental design used was Response Surface Methode (RSM) and Central Composite Design (CCD) of four factors. The analysis of resulted response surface indicated that the optimum conditions at MES production from methyl ester of PKO was obtained from the reaction temperature of 96,5oC, the sulphonation time of 4,3 hours, the methanol concentration of 26,6%, and the purification temperature of 45,5oC. The result of validation of optimum condition showed the acid value of 16,32 mg KOH/g sample and iodine value of 7,84 g iodine / 100 g sample. Keywords: Sulphonation, iodine value, acid value, Palm Kernel Oil